Preparation method of Pt + NiRE-gamma / gamma'coating for protecting nickel-based superalloy and inhibiting formation of diffusion holes
By first electroplating the Ni+RE layer on the surface of the nickel-based high-temperature alloy, then electroplating the Pt layer, and vacuum diffusion annealing, the hole problem caused by mismatch between elements is solved, and the coating's resistance to high-temperature oxidation and corrosion resistance is significantly improved. , extends the service life of the coating.
Patent Information
- Application Number
- CN202411292648.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
After vacuum annealing, the surface of nickel-based high-temperature alloys is not matched in the elemental interdiffusion rate, resulting in a large number of holes inside the coating, shortening the coating service life.
The method of first plating a Ni+RE layer, then plating the Pt layer, and then vacuum diffusion annealing is adopted. The Ni+RE layer compensates for the mismatch of elements interdiffusion between the alloy and the plating layer, and suppresses the formation of diffusion holes.
It effectively inhibits the formation of diffusion holes inside the coating, improves the resistance to high-temperature oxidation and corrosion resistance of nickel-based high-temperature alloys, and extends the service life of the coating.
Smart Images

Figure CN119145015A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-temperature alloy protective coatings, and in particular to a method for preparing a Pt+NiRE-γ / γ' coating for protecting nickel-based high-temperature alloys and inhibiting the formation of diffusion holes. Background Art
[0002] Nickel-based superalloy is a material with excellent performance under extreme conditions such as high temperature and high pressure, and is widely used in aviation, energy and other fields. Nickel-based superalloy exhibits excellent mechanical properties at high temperatures, but due to the continuous reduction of the content of high-temperature corrosion-resistant elements (Al and Cr) in the iterative improvement process, it is difficult to form a protective oxide film (such as α-Al2O3) on the alloy surface in harsh service environments. Therefore, the high-temperature oxidation resistance and hot corrosion resistance of the alloy are generally provided by the high-temperature protective coating applied to the surface. Adding Pt group elements (such as Pt, Pd) or some active elements (REs, such as Hf, Ce, Y, etc.) to the aluminide coating will change the oxidation mechanism of the coating.
[0003] As a modifying element, Pt element has been widely used in high-temperature protective coatings at this stage. Its main roles in resisting high-temperature oxidation are as follows: 1. Pt element can inhibit the growth of voids at the oxide film-metal interface, which is beneficial to improving the bonding strength between the Al2O3 film and the coating; 2. Pt element can effectively promote the formation of a single α-Al2O3 oxide film, and Pt has a strong affinity with Al element, which is beneficial to the uphill diffusion of Al element in the matrix and helps to form a continuous and dense alumina protective film on the surface; 3. The presence of Pt element can reduce the critical aluminum content required to generate α-Al2O3 oxide film, which can ensure the continuous formation of alumina protective film; 4. The presence of Pt element can inhibit the outward diffusion of refractory alloy elements (W, Mo and other elements) and reduce the harm of S element.
[0004] Active elements (REs, such as Hf, Ce, Y, etc.) added to high-temperature protective coatings will improve the adhesion of the oxide film generated during high-temperature oxidation. Current research believes that during high-temperature oxidation, the mechanism by which active elements improve the adhesion of Al2O3 films is mainly reflected in the following aspects: 1. Inhibiting the generation and growth of holes at the oxide film / alloy matrix interface; 2. Generating active element oxides at the oxide film / alloy matrix interface to increase the contact area between the oxide film and the alloy matrix; 3. Relieving the wrinkling phenomenon of the oxide film; 4. Directly participating in the bonding of the oxide film / alloy matrix interface to improve the interface bonding ability.
[0005] Pt diffusion γ / γ' coating is a coating used for surface protection of nickel-based high-temperature alloys, which can effectively improve the high-temperature oxidation resistance and corrosion resistance of the alloy. Pt diffusion γ / γ' coating can be prepared by electroplating 5-8μm Pt and then performing diffusion treatment. Compared with β-(Ni,Pt)Al coating, γ / γ' coating has potential advantages such as higher creep strength, better compatibility between coating and high-temperature alloy substrate, and low manufacturing cost. However, there is still a common problem in the preparation process of this coating: when the Pt layer is electroplated on the surface of the nickel-based high-temperature alloy and then vacuum annealed, a large number of holes are generated inside the coating after vacuum annealing due to the different mutual diffusion rates between the elements inside the alloy substrate and the Pt elements in the coating. When the high-temperature alloy workpiece is subjected to cyclic loading stress, the holes inside the coating will become fatigue crack sources, greatly shortening the service life of the coating. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a Pt+NiRE-γ / γ' coating for protecting nickel-based high-temperature alloys and inhibiting the formation of diffusion holes. The Pt diffusion γ / γ' coating is improved by first composite electroplating a Ni+RE layer, then electroplating a Pt layer, and then performing vacuum diffusion annealing. The presence of the Ni+RE layer compensates for the problem of mismatched mutual diffusion of elements between the alloy and the coating, inhibits the formation of diffusion holes, and solves the problems existing in the above-mentioned prior art.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] One of the technical solutions of the present invention is to provide a Pt+NiRE-γ / γ' coating suitable for protecting nickel-based high-temperature alloys, wherein the elements of the Pt+NiRE-γ / γ' coating include Ni, Al, Pt and RE; wherein Ni and Al constitute γ'-Ni3Al and γ-Ni phases, and Pt and RE elements are dissolved in the γ'-Ni3Al and γ-Ni phases.
[0009] Furthermore, the mass ratio of Ni, Al, Pt and RE is 60-70:20-25:8-11:1-4
[0010] Furthermore, the RE includes Hf and / or Y.
[0011] The second technical solution of the present invention is to provide a method for preparing the above-mentioned Pt+NiRE-γ / γ' coating suitable for protecting nickel-based high-temperature alloys, the steps comprising:
[0012] After pre-treatment, the sample is placed in a nickel plating suspension containing RE powder, and a Ni+RE layer is obtained by a first electroplating to obtain a first electroplated sample;
[0013] Placing the first electroplating sample in a Pt plating solution, and obtaining a Pt layer by a second electroplating to obtain a second electroplating sample;
[0014] The second electroplated sample is subjected to vacuum diffusion annealing to obtain the Pt+NiRE-γ / γ' coating;
[0015] The sample is a nickel-based high-temperature alloy containing aluminum.
[0016] Furthermore, the aluminum-containing nickel-based high-temperature alloy is an aluminum-containing nickel-based single crystal alloy.
[0017] Furthermore, the pretreatment step includes: grinding, sandblasting, ultrasonic cleaning, electrochemical degreasing and activation treatment of the sample in sequence.
[0018] Preferably, the polishing is performed using SiC sandpapers of 400, 1000 and 2000 meshes in sequence.
[0019] When grinding, the edges of the sample should be chamfered to prevent stress concentration at the edges from causing cracking during the coating preparation process or premature peeling of the surface oxide film during the sample oxidation process.
[0020] Preferably, the sandblasting is wet sandblasting using 150 mesh alumina shots.
[0021] Preferably, the ultrasonic cleaning is performed in deionized water, alcohol and acetone for 20 minutes respectively.
[0022] Preferably, the electrochemical degreasing step is: electrochemical degreasing in a sodium hydroxide solution with a concentration of 5 to 15 g / L, with the sample as the cathode and the stainless steel plate as the anode, at a current density of 2 to 15 A / dm 2 Treat for 1 to 10 minutes.
[0023] Preferably, the activation treatment step is: placing the sample in an activation solution for treatment for 0.5 to 5 minutes; the activation solution is an aqueous solution of hydrochloric acid and phosphoric acid, wherein the concentration of hydrochloric acid in the activation solution is 10 to 30 vol.%, and the concentration of phosphoric acid is 5 to 25 vol.%.
[0024] Furthermore, the nickel plating suspension containing RE powder includes: 150-180 g / L NiSO4·6H2O, 8-15 g / L NaCl, 30-60 g / L H3BO3, 110 g-130 g / L Na2SO4, 0.1-0.2 g / L sodium dodecyl sulfate and 0-20 g / L RE, and the content of RE is not 0.
[0025] The solvent of the suspension of nickel plating and RE powder is water, and the pH is 4.0 to 6.0.
[0026] Furthermore, the electroplating temperature of the first electroplating is 30-40°C, and the current density is 4-12 mA / cm 2 , time is 0.5h~2h.
[0027] Furthermore, the thickness of the Ni+RE layer is 5-8 μm.
[0028] Furthermore, the Pt plating solution includes: 5 to 15 g / L of dinitrodiammine platinum and 5 to 15 g / L of sodium nitrite.
[0029] The solvent of the Pt plating solution is water, and the pH value is adjusted to 8.0-10.0 using aqueous ammonia.
[0030] Furthermore, the second electroplating process has an electroplating temperature of 70 to 80°C and a current density of 4 to 6 mA / cm 2 , time is 2h~4h.
[0031] Furthermore, the thickness of the Pt layer is 5 to 8 μm.
[0032] Furthermore, the steps of the vacuum diffusion annealing treatment are: vacuum seal the second electroplated sample, then heat it to 480-500°C at a heating rate of 5-10°C / min, keep it warm for 2-2.5h, then heat it to 1080-1100°C at a heating rate of 5-10°C / min, keep it warm for 3.5-4h, and cool it to room temperature in the furnace.
[0033] Furthermore, the thickness of the Pt+NiRE-γ / γ' coating is 10-30 μm.
[0034] During the vacuum diffusion annealing process, the Ni+RE layer and the Pt layer interdiffused with the alloy to form a Pt+NiRE-γ / γ' coating, and the thickness of the coating increased compared with that before vacuum diffusion annealing.
[0035] The third technical solution of the present invention is to provide an application of the above-mentioned Pt+NiRE-γ / γ' coating suitable for protecting nickel-based high-temperature alloys in the protection of nickel-based high-temperature alloys.
[0036] Furthermore, the application in the protection of nickel-based high-temperature alloys includes the use of the Pt+NiRE-γ / γ' coating as a high-temperature oxidation / corrosion protection coating or a thermal barrier coating bonding layer for nickel-based high-temperature alloys.
[0037] Among them, the high temperature oxidation / corrosion resistant protective coating refers to a coating that has both high temperature oxidation resistance and corrosion resistance.
[0038] Technical solution 4 of the present invention: provides a method for inhibiting the formation of diffusion holes in Pt diffusion γ / γ' coatings, first electroplating a Ni+RE layer on the surface of the nickel-based high-temperature alloy, then electroplating a Pt layer, and then performing vacuum diffusion annealing.
[0039] The present invention discloses the following technical effects:
[0040] The present invention uses the γ / γ' phase similar to the main phase of the nickel-based high-temperature alloy as the main phase, and modifies the coating with Pt and active elements RE. The coating is prepared by composite plating Ni+RE and electroplating Pt and then diffusion annealing, which inhibits the formation of diffusion holes in the coating and protects the mechanical properties of the coating and the alloy. The modification of the Pt element can promote the formation of a protective Al2O3 film on the surface of the coating, inhibit the S segregation behavior at the interface of the coating, and enhance the oxidation resistance of the coating. The addition of active elements can pin the oxide film, inhibit the aggregation of holes at the interface of the oxide film, and enhance the bonding force between the oxide film and the coating interface. As a result, the Pt+NiRE-γ / γ' coating has excellent high-temperature oxidation and corrosion resistance at high temperatures. On the other hand, since the coating phase is similar to the phase in the alloy, the mutual diffusion between the coating and the alloy can be avoided during the service of the coating, and the formation of the TCP phase can be inhibited, so as to achieve the effect of maintaining the stability of the alloy structure.
[0041] The present invention adopts an electroplating method to apply two coatings, Ni and Pt, on the surface of a substrate, with low preparation cost. The two coating structures are diffused and annealed to suppress the formation of diffusion holes inside the coatings. The coatings are modified by Pt and active elements, thereby enhancing the ability of the coatings to form a protective oxide film and improving the anti-stripping performance of the oxide film. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0043] Figure 1 The SEM images of the coating surfaces of Examples 1 to 2 and Comparative Examples 1 to 2 before annealing treatment, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Example 1, and (d) is Example 2;
[0044] Figure 2 The morphology diagrams of the cross sections of the coatings of Examples 1 to 2 and Comparative Examples 1 to 2 before annealing treatment, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Example 1, and (d) is Example 2;
[0045] Figure 3 The cross-sectional morphology diagrams of the coatings after annealing treatment of Examples 1-2 and Comparative Examples 1-2, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Example 1, and (d) is Example 2;
[0046] Figure 4 XRD diagrams of the coatings after annealing treatment of Examples 1-2 and Comparative Examples 1-2, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Example 1, and (d) is Example 2;
[0047] Figure 5 The cross-sectional morphology diagrams of the samples after annealing treatment in Examples 1 to 2 and Comparative Example 1 after 100 h of cyclic oxidation at 1000° C., wherein (a) is Comparative Example 1, (b) is Example 1, and (c) is Example 2;
[0048] Figure 6 XRD diagrams of the coatings of the samples after annealing treatment in Examples 1 to 2 and Comparative Example 1 after cyclic oxidation at 1000° C. for 100 h, wherein (a) is Comparative Example 1, (b) is Example 1, and (c) is Example 2;
[0049] Figure 7 The weight gain curve of the coating mass of the samples after annealing treatment in Examples 1 to 2 and Comparative Example 1 after 100 hours of cyclic oxidation at 1000°C. DETAILED DESCRIPTION
[0050] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0051] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0052] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0053] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0054] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0055] The raw materials and reagents used in the specific implementation of the present invention are all commercially available products, among which the second-generation nickel-based single crystal high-temperature alloy N5 is provided by the Institute of Metal Research, Chinese Academy of Sciences, and the grade is N5 alloy.
[0056] Example 1
[0057] Preparation of Pt+NiHf-γ / γ' coating:
[0058] S1. The substrate sample used is the second generation nickel-based single crystal high temperature alloy N5, and the sample size is Φ16mm×2.5mm. The substrate sample is polished, sandblasted, ultrasonically cleaned, electrochemically degreased and activated in sequence to obtain a pretreated sample;
[0059] The grinding process is to grind the substrate sample with SiC sandpaper of 400, 1000 and 2000 meshes in sequence; the sandblasting process is to wet sandblast the substrate sample with 150 mesh alumina pellets; the substrate sample is ultrasonically cleaned in deionized water, alcohol and acetone for 20 minutes respectively; the electrochemical degreasing process is to electrochemically degreasing the substrate sample in a sodium hydroxide solution with a concentration of 7 g / L, with the substrate sample as the cathode and the stainless steel plate as the anode, at a current density of 8 A / dm 2 The activation treatment is to place the substrate sample in the activation solution for 2 minutes; the activation solution is an aqueous solution of hydrochloric acid and phosphoric acid, wherein the concentration of hydrochloric acid in the activation solution is 15 vol.%, and the concentration of phosphoric acid is 15 vol.%;
[0060] S2. Electroplating Ni+Hf layer, the plating solution composition is NiSO4·6H2O 152g / L, NaCl 14g / L, H3BO3 37g / L, Na2SO4 111g / L, sodium dodecyl sulfate 0.2g / L, Hf 20g / L, the balance is deionized water; the pH value of the plating solution is adjusted to 5, and the pretreated sample is electroplated with an AC power supply. The electroplating is carried out in a magnetic stirrer with a stirring speed of 5r / min. The entire electroplating process is kept at a constant temperature. The temperature during electroplating is controlled at 40°C and the current density is controlled at 10mA / cm 2During the whole electroplating process, the pH value of the electroplating solution is maintained within the range of 5 to 7, and the thickness of the electroplated Ni+Hf layer is 6 μm, thereby obtaining a first electroplated sample;
[0061] S3, electroplating Pt layer, the plating solution composition is dinitrosodiammine platinum 5.5g / L and sodium nitrite 14g / L, the balance is deionized water, the pH value of the plating solution is adjusted to 9 with ammonia water, the first electroplating sample is electroplated with AC power supply, the electroplating is carried out in a magnetic stirrer, the stirring speed is 2r / min, the whole electroplating process is kept at a constant temperature, the temperature is controlled at 80℃, the current density is controlled at 5mA / cm 2 During the whole electroplating process, the pH value of the electroplating solution was kept within the range of 8 to 10, and the thickness of the electroplated Pt layer was 7.9 μm, thereby obtaining a second electroplated sample;
[0062] S4. The second electroplated sample is vacuum sealed and placed in a muffle furnace for annealing: the temperature is first increased to 500°C at a heating rate of 10°C / min and kept at this temperature for 2 hours, then the temperature is increased to 1080°C at a heating rate of 5°C / min and kept at this temperature for 4 hours, and then the sample is cooled to room temperature in the furnace to obtain a sample with a Pt+NiHf-γ / γ' coating.
[0063] Example 2
[0064] Preparation of Pt+NiY-γ / γ' coating:
[0065] S1, the same as step S1 of Example 1, obtaining a pretreated sample;
[0066] S2. Electroplating Ni+Y layer, the plating solution composition is NiSO4·6H2O 170g / L, NaCl 15g / L, H3BO3 40g / L, Na2SO4 130g / L, sodium dodecyl sulfate 0.2g / L, Y 20g / L, the balance is deionized water; the pH value of the plating solution is adjusted to 5, and the pretreated sample is electroplated with an AC power supply. The electroplating is carried out in a magnetic stirrer with a stirring speed of 5r / min. The entire electroplating process is kept at a constant temperature. The temperature during electroplating is controlled at 40°C and the current density is controlled at 10mA / cm 2 During the whole electroplating process, the pH value of the electroplating solution is maintained within the range of 5 to 7, and the thickness of the electroplated Ni+Y layer is 6 μm, thereby obtaining a first electroplated sample;
[0067] S3, electroplating Pt layer, the plating solution composition is 8.5g / L dinitrosodiammine platinum and 14g / L sodium nitrite, the balance is deionized water, the pH value of the plating solution is adjusted to 9 with ammonia water, the first electroplating sample is electroplated with AC power supply, the electroplating is carried out in a magnetic stirrer, the stirring speed is 2r / min, the whole electroplating process is kept at a constant temperature, the temperature is controlled at 80℃, the current density is controlled at 5mA / cm2 During the whole electroplating process, the pH value of the electroplating solution was kept within the range of 8 to 10, and the thickness of the electroplated Pt layer was 7.9 μm, thereby obtaining a second electroplated sample;
[0068] S4. The second electroplated sample is sealed in a vacuum tube and placed in a muffle furnace for annealing: the temperature is first increased to 500°C at a heating rate of 10°C / min and kept at this temperature for 2 hours, then the temperature is increased to 1080°C at a heating rate of 5°C / min and kept at this temperature for 4 hours, and then the sample is cooled to room temperature in the furnace to obtain a sample with a Pt+NiY-γ / γ' coating.
[0069] Comparative Example 1
[0070] Preparation of conventional Pt+Hf-γ / γ' coating:
[0071] S1. The substrate sample used is the second generation nickel-based single crystal high temperature alloy N5, and the sample size is Φ16mm×2.5mm. The substrate sample is polished, sandblasted, ultrasonically cleaned, electrochemically degreased and activated in sequence to obtain a pretreated sample;
[0072] The grinding process is to grind the substrate sample with SiC sandpaper of 400, 1000 and 2000 meshes in sequence; the sandblasting process is to wet sandblast the substrate sample with 150 mesh alumina pellets; the substrate sample is ultrasonically cleaned in deionized water, alcohol and acetone for 20 minutes respectively; the electrochemical degreasing process is to electrochemically degreasing the substrate sample in a sodium hydroxide solution with a concentration of 7 g / L, with the substrate sample as the cathode and the stainless steel plate as the anode, at a current density of 8 A / dm 2 The activation treatment is to place the substrate sample in the activation solution for 2 minutes; the activation solution is an aqueous solution of hydrochloric acid and phosphoric acid, wherein the concentration of hydrochloric acid in the activation solution is 15 vol.%, and the concentration of phosphoric acid is 15 vol.%;
[0073] S2. Electroplating Pt+Hf layer, the plating solution composition is dinitrosodiammine platinum 9g / L, sodium nitrite 10g / L, Hf 20g / L, the balance is water; the pH of the plating solution is adjusted to 9 with ammonia water, and the pretreated sample is electroplated with an AC power supply. The electroplating is carried out in a magnetic stirrer with a stirring speed of 2r / min. The entire electroplating process is kept at a constant temperature. The temperature during electroplating is controlled at 80°C and the current density is controlled at 5mA / cm 2 During the whole electroplating process, the pH value of the electroplating solution was kept within the range of 8 to 10, the thickness of the electroplated Pt+Hf layer was 7.5 μm, and an electroplated sample was obtained;
[0074] S3. The electroplated sample was sealed in a vacuum tube and placed in a muffle furnace for annealing. The temperature was first increased to 500°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. The temperature was then increased to 1080°C at a heating rate of 5°C / min and kept at this temperature for 4 hours. The sample was cooled to room temperature in the furnace to obtain a sample with a Pt+Hf-γ / γ' coating.
[0075] Comparative Example 2
[0076] Preparation of Pt+Ni-γ / γ' coating:
[0077] S1. The substrate sample used is the second generation nickel-based single crystal high temperature alloy N5, and the sample size is Φ16mm×2.5mm. The substrate sample is polished, sandblasted, ultrasonically cleaned, electrochemically degreased and activated in sequence to obtain a pretreated sample;
[0078] The grinding process is to grind the substrate sample with SiC sandpaper of 400, 1000 and 2000 meshes in sequence; the sandblasting process is to wet sandblast the substrate sample with 150 mesh alumina pellets; the substrate sample is ultrasonically cleaned in deionized water, alcohol and acetone for 20 minutes respectively; the electrochemical degreasing process is to electrochemically degreasing the substrate sample in a sodium hydroxide solution with a concentration of 7 g / L, with the substrate sample as the cathode and the stainless steel plate as the anode, at a current density of 8 A / dm 2 The activation treatment is to place the substrate sample in the activation solution for 2 minutes; the activation solution is an aqueous solution of hydrochloric acid and phosphoric acid, wherein the concentration of hydrochloric acid in the activation solution is 15 vol.%, and the concentration of phosphoric acid is 15 vol.%;
[0079] S2, electroplating Ni layer, the electroplating solution composition is NiSO4·6H2O 150g / L, NaCl 10g / L, H3BO3 32g / L, Na2SO4124g / L, sodium dodecyl sulfate 0.15g / L, the balance is deionized water; the pH value of the electroplating solution is adjusted to 5, and the pretreated sample is electroplated with an AC power supply. The electroplating is carried out in a magnetic stirrer with a stirring speed of 5r / min; the entire electroplating process is kept at a constant temperature, the temperature is controlled at 40°C, and the current density is controlled at 10mA / cm 2 During the whole electroplating process, the pH value of the electroplating solution is maintained within the range of 5 to 7, and the thickness of the electroplated Ni layer is 8 μm, thereby obtaining a first electroplated sample;
[0080] S3, electroplating Pt layer, the electroplating solution composition is dinitrodiammine platinum 7.5g / L and sodium nitrite 11g / L, the balance is deionized water, the pH value of the electroplating solution is adjusted to 9 with ammonia water, and then the first electroplating sample is electroplated with an AC power supply. The electroplating is carried out in a magnetic stirrer with a stirring speed of 2r / min. The entire electroplating process is kept at a constant temperature. The temperature during electroplating is controlled at 80°C and the current density is controlled at 5mA / cm 2 During the whole electroplating process, the pH value of the electroplating solution was kept within the range of 8-10, and the thickness of the electroplated Pt layer was 8.2 μm, thereby obtaining a second electroplated sample;
[0081] S4. The second electroplated sample was vacuum sealed and placed in a muffle furnace for annealing. The temperature was first increased to 500°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. The temperature was then increased to 1080°C at a heating rate of 5°C / min and kept at this temperature for 4 hours. The sample was cooled to room temperature in the furnace to obtain a sample with a Pt+Ni-γ / γ' coating.
[0082] Test example
[0083] Figure 1 The SEM images of the coating surfaces of Examples 1-2 and Comparative Examples 1-2 before annealing treatment are shown in Figures 1-2, 1-2, 2-3, 3-4, 4-5, 5-6, 6-7, 7-8, 8-9, 9-10, 11-12, 12-13, 13-14, 15-16, 17-18, 19-20, Figure 1 It can be seen that both the comparative example and the example have typical spherical protrusion morphology, proving that the Pt layer is successfully electroplated to the surface. The modification of the Pt element can promote the formation of a protective Al2O3 film on the coating surface, inhibit the S segregation behavior at the coating interface, and enhance the anti-oxidation performance of the coating.
[0084] Figure 2 The morphology of the cross-section of the coating of Examples 1-2 and Comparative Examples 1-2 before annealing treatment, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Example 1, and (d) is Example 2. Figure 2 It can be seen that the Pt layer of the comparative example and the embodiment is closely attached to the coating layer.
[0085] Figure 3 The cross-sectional morphology of the coatings after annealing treatment of Examples 1-2 and Comparative Examples 1-2, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Example 1, and (d) is Example 2. Figure 3 It can be seen that after comparing (b), (c) and (d) with (a), it can be found that the cross-sectional morphology of (a) contains a large number of diffusion holes, while the number of diffusion holes contained in the cross-sectional morphology of (b), (c) and (d) is greatly reduced.
[0086] Figure 4The XRD patterns of the coatings after annealing in Examples 1-2 and Comparative Examples 1-2, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Example 1, and (d) is Example 2. Figure 4 It can be seen that both the comparative example and the embodiment are typical γ'-Ni3Al phases, and the coating phase is similar to the phase in the alloy. During the service of the coating, the mutual diffusion between the coating and the alloy can be avoided, the formation of the TCP phase can be inhibited, and the effect of maintaining the stability of the alloy structure can be achieved.
[0087] Figure 5 The cross-sectional morphology of the samples after annealing in Examples 1-2 and Comparative Example 1 after 100 hours of cyclic oxidation at 1000°C, wherein (a) is Comparative Example 1, (b) is Example 1, and (c) is Example 2. Figure 5 It can be seen that no holes are generated at the interface of the coatings of Examples 1 to 2. Since the hole generation of the coatings is significantly suppressed, the bonding strength between the coatings and the substrate is better to a certain extent.
[0088] Figure 6 The XRD patterns of the coatings of the samples annealed in Examples 1 to 2 and Comparative Example 1 after 100 hours of cyclic oxidation at 1000°C are shown in Figure 1, where (a) is Comparative Example 1, (b) is Example 1, and (c) is Example 2. Figure 6 It can be seen that all three have generated Al2O3 protective films, and Comparative Example 1 has also generated HfO2.
[0089] Figure 7 The weight gain curve of the coating after 100 hours of cyclic oxidation at 1000°C for the samples annealed in Examples 1-2 and Comparative Example 1 (Pt+HF is Comparative Example 1, Ni+Y-Pt is Example 2, and Ni+HF-Pt is Example 1). Figure 7 It can be seen that the mass gain of Examples 1 and 2 is lower than that of Comparative Example 1. At the same time, the mass gain curves of Examples 1 and 2 enter the stable oxidation stage faster than that of Comparative Example 1, provide a stable oxide film earlier, and have better oxidation resistance. It can be seen that the improved method used for the Pt+NiRE-γ / γ' coating proposed in the present invention is simpler and more cost-effective than the existing technology, and can significantly inhibit the generation of diffusion holes inside the coating.
[0090] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A Pt+NiRE-γ / γ' coating suitable for protecting nickel-based high-temperature alloys, characterized in that: The elements of the Pt+NiRE-γ / γ' coating include Ni, Al, Pt and RE; wherein Ni and Al constitute γ'-Ni3Al and γ-Ni phases, and Pt and RE elements are dissolved in the γ'-Ni3Al and γ-Ni phases.
2. The Pt+NiRE-γ / γ' coating according to claim 1, characterized in that: The mass ratio of Ni, Al, Pt and RE is 60-70:20-25:8-11:1-4.
3. The Pt+NiRE-γ / γ' coating according to claim 1 or 2, characterized in that: The RE includes Hf and / or Y.
4. A method for preparing a Pt+NiRE-γ / γ' coating according to any one of claims 1 to 3, characterized in that the steps include: After pre-treatment, the sample is placed in a nickel plating suspension containing RE powder, and a Ni+RE layer is obtained by a first electroplating to obtain a first electroplated sample; Placing the first electroplating sample in a Pt plating solution, and obtaining a Pt layer by a second electroplating to obtain a second electroplating sample; The second electroplated sample is subjected to vacuum diffusion annealing to obtain the Pt+NiRE-γ / γ' coating; The sample is a nickel-based high-temperature alloy containing aluminum.
5. The preparation method according to claim 4, characterized in that: The pretreatment steps include: grinding, sandblasting, ultrasonic cleaning, electrochemical degreasing and activation treatment of the sample in sequence.
6. The preparation method according to claim 4, characterized in that: The nickel plating suspension containing RE powder comprises: 150-180 g / L NiSO4·6H2O, 8-15 g / L NaCl, 30-60 g / L H3BO3, 110 g-130 g / L Na2SO4, 0.1-0.2 g / L sodium dodecyl sulfate and 0-20 g / L RE, and the content of RE is not 0; the electroplating temperature of the first electroplating is 30-40°C, and the current density is 4-12 mA / cm 2 , time is 0.5h~2h; the thickness of the Ni+RE layer is 5~8μm.
7. The preparation method according to claim 4, characterized in that: The Pt plating solution includes: 5-15 g / L dinitrodiammine platinum and 5-15 g / L sodium nitrite; the second electroplating temperature is 70-80°C, and the current density is 4-6 mA / cm 2 , time is 2h~4h; the thickness of the Pt layer is 5~8μm.
8. The preparation method according to claim 4, characterized in that: The steps of the vacuum diffusion annealing treatment are: vacuum seal the second electroplated sample, then heat it to 480-500°C at a heating rate of 5-10°C / min, keep it warm for 2-2.5 hours, then heat it to 1080-1100°C at a heating rate of 5-10°C / min, keep it warm for 3.5-4 hours, and cool it to room temperature in the furnace.
9. Use of the Pt+NiRE-γ / γ' coating according to any one of claims 1 to 3 in the protection of nickel-based high-temperature alloys.
10. A method for inhibiting the formation of diffusion holes in a Pt diffusion γ / γ' coating, characterized in that: A Ni+RE layer is first electroplated on the surface of the nickel-based high-temperature alloy, and then a Pt layer is electroplated, and then vacuum diffusion annealing is performed.
Citation Information
Patent Citations
Method for introducing rare metal Hf element into coating
CN106283135A
Hf modified PtAl coating and preparation method and application thereof
CN110735162A
Preparing method used for single-crystal high-temperature alloy low-diffusion single-phase platinum aluminum coating
CN111636079A
Methods for making high-temperature coatings having Pt metal modified gamma-Ni + gamma'-Ni3Al alloy compositions and a reactive element
US20060127695A1
